The Effect of Influencer and Consumer Reviews on Purchase Intention on Brand Compass - Iqbal Muhammad Alghiffari; Sari Listyorini; Widiartanto (Sekolah Pascasarjana Universitas Brawijaya, 2022)
Social media is one of the tools of communication or information of the current digital age, making it much easier for people to obtain information. The current healthy social media phenomenon is affecting people's consumption significantly. Influencer has become a very effective and effective way of spotting a strong relationship between brand and their consumer. Leverage is viewed as highly effective in establishing strong relationships between brand and consumer. The study was intended to identify the influence of variable consumer reviewers and influence diluted to purchase mechanisms. The study is a quantitative study involving 400 respondents and using partial data analysis techniques at least square (PLS). The results of the study stated that consumer review and influence influence each other have an influence on purchase and productivity. Keywords: influencer, consumer review, media social